Oils seeds performed better for different sources of irrigation water as compared to wheat and chickpeas in Malaprabha Command Area of Northern Karnataka: Oils seeds performed better for different sources of irrigation water as compared to wheat and chickpeas in Malaprabha Command Area of Northern Karnataka - U K SHANWAD; B C PUNITHA; G B SHASHIDHAR; KUMAR LAMANI (Journal of Oilseeds Research, 2023)
In the present scenario of irregular monsoon, in-situ conservation of rain water through farm ponds and providing life saving irrigations utilizing ground water to the agriculture crops is the need of hour. In this context, a study was conducted on evaluation of effect of different sources of irrigation water on important rabi crops like safflower, sunflower, wheat and chickpea during rabi seasons of 2017, 2018 & 2019 at the Irrigation Water Management Research Center (IWMRC), Belavatagi in North Karnataka. Among the different rabi crops tried safflower recorded significantly higher chickpea equivalent yield in all three years as well as in pooled analysis (2.38, 2.04, 1.16 and 1.86 t /ha, respectively) followed by sunflower (1.49, 1.32, 1.28 and 1.36 t /ha, respectively). The results also indicated that, among the rabi crops, safflower and sunflower are the least affected crops with respect to sources of irrigation water, whereas chickpea and wheat are much affected with the different sources of irrigation water. Thus, oilseeds like safflower and sunflower performed better as compared to chickpea and wheat with different sources of irrigation water with respect to their growth and performance in Malaprabha Command Area of North Karnataka region.